Antimicrobial Susceptibility Patterns and Occurrence of Multidrug-Resistant Bacteria among Patients and Healthcare Workers in Selected Primary Healthcare Centres in Kano Metropolis - Rukayya Muhammad Nura; Muhammad Yusha'u (International Journal of Advanced Academic Research, 2026)
The emergence of multidrug-resistant (MDR) bacteria in primary healthcare settings threatens the effectiveness of empirical antibiotic therapy and complicates patient management. This study determined the antimicrobial susceptibility patterns and occurrence of MDR bacteria among patients and healthcare workers (HCWs) in three primary healthcare centres (PHCs). Guringawa, Ja'en, and Murtala Muhammad Specialist Hospital in Kano Central, Nigeria. A cross-sectional survey was conducted using 400 urine and wound swab samples from patients, and urine samples from HCWs. Bacterial isolates recovered from culture were subjected to antimicrobial susceptibility testing using the Kirby–Bauer disc diffusion method on Mueller-Hinton agar, following CLSI guidelines, and isolates resistant to at least one agent in three or more antimicrobial categories were classified as multidrug resistant. Of 268 culture-positive isolates, 105 (39.2%) were confirmed as MDR, comprising Staphylococcus aureus (37.14%), Escherichia coli (26.67%), Klebsiella pneumoniae (19.05%), Proteus mirabilis (8.57%), and Pseudomonas aeruginosa (8.57%). Patients accounted for 80 (76.19%) of the MDR isolates, while HCWs contributed 25 (23.81%). High resistance was observed against ceftazidime, ceftriaxone, augmentin, erythromycin, and cefoxitin across most organisms. Imipenem retained the highest activity against Gram-negative isolates (75.0–85.7% susceptibility), while gentamicin was the most effective agent against *S. aureus* (57.1% susceptibility in patients). No statistically significant differences (p > 0.05) were observed in susceptibility patterns between patients and HCWs for any organism or antibiotic tested. These findings reveal a substantial burden of MDR bacteria circulating among both patients and healthcare workers in PHCs in Kano Metropolis, with widespread resistance to commonly prescribed antibiotics, underscoring the urgent need for antimicrobial stewardship and continuous resistance surveillance in primary healthcare settings.